3D numerical simulation of pulsed fracture in complex fracture-cavitied reservoir. (September 2020) - Wang, Yujie; Li, Xinyong; Zhao, Bing; Zhang, Zhennan
Abstract: The carbonate reservoir contains numerous randomized natural fractures and cavities. Due to the stress concentration surrounding the cavity, the conventional hydraulic fracturing technique is very hard to connect the artificial fracture with the cavity. Under such situation, the pulsed fracturing (PF) technique should be an alternative stimulation approach. To investigate the PF process in the complex fracture-cavitied reservoir, a 3D modeling method for such reservoir is developed at first. The augmented virtual internal bond is adopted for rock matrix modeling, which is a micro–macro constitutive model that intrinsically contains the fracture mechanism at the micro level. The 3D element partition method (3D-EPM) is used to model the natural fractures, which allows the crack to cut through the element without any remeshing. A 3D modeling method for the natural cavity is developed. The PF behaviors in the fracture-cavitied reservoir are investigated. It is found that the natural fracture can strongly guide the PF path. The PF can break through the stress barrier surrounding a cavity and connect this cavity to great extent, which is very helpful to improve the reservoir stimulation. The findings provide valuable reference for the design and assessment of PF treatment in the fracture-cavitied reservoir.